Building Success in Development and Peacebuilding by Caring for Carers: A Guide to Research, Policy and Practice to Ensure Effective, Inclusive and Responsive Interventions (2021)
The experiences and marginalisation of international organisation employees with caring responsibilities has a direct negative impact on the type of security and justice being built in conflict-affected environments. This is in large part because international organisations fail to respond to the needs of those with caring responsibilities, which leads to their early departure from the field, and negatively affects their work while in post. In this toolkit we describe this problem, the exacerbating factors, and challenges to overcoming it. We offer a theory of change demonstrating how caring for carers can both improve the working conditions of employees of international organisations as well as the effectiveness, inclusivity and responsiveness of peace and justice interventions. This is important because it raises awareness among employers in the sector of the severity of the problem and its consequences. We also offer a guide for employers for how to take the caring responsibilities of their employees into account when developing human resource policies and practices, designing working conditions and planning interventions.Finally, we underscore the importance of conducting research on the gendered impacts of the marginalisation of employees with caring responsibilities, not least because of the breadth and depth of resultant individual, organisational and sectoral harms.In this regard, we also draw attention to the way in which gender stereotypes and gender biases not only inform and undermine peacebuilding efforts, but also permeate research in this field. Our toolkit is aimed at international organisation employees, employers and human resources personnel, as well as students and scholars of peacebuilding and international development. We see these communities of knowledge and action as overlapping, with insights to be brought to bear as well as challenges to be overcome in this area. The content of the toolkit is equally relevant across these knowledge communities as well as between different specialisms and disciplines. Peacebuilding and development draw in experts from economics, politics, anthropology, sociology and law, to name but a few.The authors of this toolkit have come together from gender studies, political science, and development studies to develop a theory of change informed by interdisciplinary insights. We hope, therefore, that this toolkit will be useful to an inclusive and interdisciplinary set of knowledge communities. Our core argument - that caring for carers benefits the individual, the sectors, and the intended beneficiaries of interventions - is relevant for students, researchers, policy makers and practitioners alike.